Analysis of Employee Work Posture with the Quick Exposure Check (QEC) and Rapid Entire Body Assessment (REBA) Method (Case Study: CV. Wijaya Mandiri Label) - Atuna, Vincentius; Safirin, Mochammad Tutuk (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
CV Wijaya Mandiri Label is a company engaged in offset printing label printing. The products produced from the company can vary according to customer demand. The printing industry generally still uses work activities in the form of manual material handling which includes lifting, pushing, and pulling to move an object. This research aims to identify the level of potential risk of injury to employee work postures. In this study, the methods uses were Quick Exposure Check (QEC) and Rapid Entire Body Assessment (REBA). The QEC method is used as an initial identification of potential ergonomic problems and the risk of injury at workstations where the exposure level is 83% (very high risk) and 82.7% (very high risk). So that further research is needed by assessing work postures using the REBA method with REBA score 11 (very high) and REBA score 9 (high). The proposed improvements are in the form of manual scissor lift table and an adjustable work desk following the anthropometry of workers. From these tools can reduce the risk level REBA score from 11 to 7 (medium) and REBA score from 9 to 5 (medium) which is known from the simulation results of using tools using 3D software.